Supervision, Compliance, and Accountability in The Implementation of Policies on The Collection of Money or Goods at The Ministry of SocialAffairs of The Republic af Indonesia - M. Nur Afif Aulia; Susilawati Susilawati; Aribowo Aribowo (Journal Of Social Science (JoSS), 2026)
This study aimed to examine the effects of oversight of Pengumpulan Uang atau Barang (PUB) policies and institutional compliance on accountability in public donation management. The study employed a mixed-methods approach using an explanatory sequential design that combined quantitative surveys and qualitative in-depth interviews. Quantitative data were collected through questionnaires distributed to 28 PUB organizing institutions licensed by the Ministry of Social Affairs of the Republic of Indonesia, while qualitative data were obtained through interviews with two informants from the Ministry of Social Affairs and two informants from PUB organizing institutions. Data analysis was conducted using linear regression analysis, t-tests, F-tests, and the coefficient of determination, supported by thematic analysis of interview data. The results showed that policy oversight had no partial significant effect on public donation management accountability, whereas institutional compliance had a positive and significant effect. Simultaneously, oversight and compliance had a significant effect on accountability, with a coefficient of determination of 60%. Qualitative findings revealed that limited supervisory resources, the dominance of administrative approaches, and inadequate digital oversight systems were factors affecting the effectiveness of supervision. This study indicated that accountability in public donation management in the era of digital philanthropy was influenced more by the quality of internal organizational governance than by regulatory administrative supervision. These findings highlight the need to strengthen a culture of compliance, implement risk-based supervision, and establish regulatory reforms that are more adaptive to the development of digital philanthropy in Indonesia.